BEBEBERAPA KAJIAN TENTANG HUSEIN MUHAMMAD TERKAIT PENAFSIRAN AL-QUR’AN - Mursyid, Ali (Moderation | Journal of Islamic Studies Review, 2023)
K.H. Husein Muhammad or known as Buya Husein, as is known, is a religious figure (Kiai) with a traditional Islamic education background, who persistently discusses and fights for gender equality discourse. Buya Hussein's thoughts and steps in defending these women attracted a lot of attention from the Adameiks, to discuss it and research it. In this article, several studies and studies conducted by academics are presented, to discuss and study the thoughts of Buya Husein. Specifically related to studies and studies associated with the interpretation of the Qur'an Buya Hussein. Actually, there have been many studies and studies on Buya Hussein, but what is conveyed in this article, only a few. This is intended as a first step to collect and map various studies and research on the thought of Hussein Muhammad.